The outcomes of our patients operated for hyperparathyroidism - ATAKAN, Sezer; İBİŞ, Cem and İRFANOĞLU, Mehmet Emin (Cerrahpaşa Medical Journal, 2014)
In this study, 36 patients who underwent parathyroidectomy operation due to hyperparathyroidism between 1998- 2006 in Trakya University Medical Faculty Department of General Surgery were retrospectively evaluated. There were 26 (72 %) female and 10 (28 %) male patients. The mean age was 46.6 (17-75 years). The complaints of the patients were bone and/or joint pains, osteoporosis, dysuria, dyspepsia, and hypertension. Preoperative diagnosis was made in all of the patients thorough the neck ultrasonographic evaluation and 99mTc-M‹B‹ parathyroid scintigraphy. Another 7 (19 %) patients had an additional magnetic resonance imaging scan, and 4 (11 % 9) had an additional computed tomography scan of the neck. The levels of serum calcium, phosphorus, parathormone, alkaline phosphatase were investigated in all of the patients. All of the patients underwent bilateral neck exploration and one patient was reoperated due to recurrent disease. Although hyperparathyroidism is such an easy diagnosed and frequently seen illness, many clinicians dismiss this pathology. Patients with hyperparathyroidism tried to be investigated and treated in different clinics due to the large variety of symptoms. However patients with hyperparathyroidism should be treated by a multidisciplinary team consisting of general surgeon, endocrinologist, nuclear medicine specialist, and radiologist.